Navigating a Colonial Legacy and Issues of Race and Racism as a South African Social Work Academic - Motloung, Siphiwe (Southern African Journal of Social Work and Social Development)
A colonial legacy, the nature of which subliminally instils ingrained reproductions of racial inferiority and superiority, makes it necessary to highlight the need to focus in more depth on the race and racism discourse of social work academics. As social work educators within the current South African higher education, the importance of social justice cannot be overemphasised. Considering the colonial undertones of South African social work education and the multicultural nature of South African society, in this article, I focus on the ethical implications of a colonial legacy and lingering race and racism issues for social work education. The article is derived from part of a qualitative study on discourses about race and racism with 16 academics within the higher education arena. In the article, I employed a non-probability sampling method, face-to-face interviews and a discursive data analysis approach. An excerpt of the interview with one academic Claire (white) is analysed by the researcher (black) with specific focus on Claire’s race and racism discourse. The focus is on critically and reflexively engaging with the ethical implications this has for social work education in the current era. It also contains my reflections as a social work academic navigating issues of race and racism. The findings evidenced seeming obliviousness to coloniality for Claire, which I inadvertently channel. This reflects the challenges of the South African commitment to moving beyond colonialism and the challenge this poses for social work values and ethics.